A Sequential Debonding Fracture Model for Hydrogen‐Bonded Hydrogels. Issue 19 (29th August 2018) - Xin, Hai; Oveissi, Farshad; Naficy, Sina; Spinks, Geoffrey M.
ABSTRACT: Hydrogen bonds are known to play an important role in prescribing the mechanical performance of certain hydrogels such as polyether‐based polyurethanes. The quantitative contribution of hydrogen bonds to the toughness of polymer networks, however, has not been elucidated to date. Here, a new physical model is developed to predict the threshold fracture energies of hydrogels physically crosslinked via hydrogen bonds. The model is based on consecutive and sequential dissociation of hydrogen‐bonded crosslinks during crack propagation. It is proposed that the scission of hydrogen bonds during crack propagation allows polymer strands in the deformation zone to partially relax and release stored elastic energy. The summation of these partial chain relaxations leads to amplified threshold fracture energies which are 10–45 times larger than those predicted by the classical Lake–Thomas theory. Experiments were performed on a hydrophilic polyurethane hydrogel where urea additions were used to control the density of hydrogen bonds. The measured fracture energies were in good agreement with the calculated values. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1287–1293 Abstract : Hydrogen‐bonded hydrogels are easily fabricated highly swollen polymer networks that are mechanically robust. The origin of their high toughness is explored by using urea to control the density of hydrogen bonds. The gel toughness is shown to be much greater than predicted by the classical Lake‐Thomas theory. A new model supported by experiments is introduced based on the sequential debonding of successive hydrogen bonds along polymer chains that span the crack plane.